PENYULUHAN PEMBUATAN SPRAY ANTINYAMUK DARI SERAI (Cymbopogon citrates) DI PAKUAN BARU JAMBI - Rizky Yulion; Oliyen Madori; Nike Nur Ahdiyah; Sella Julia Ananda; Debora Dwi Hardiyanti; Retno Agustia Ningsih; Fresha Nurmayora; Yollanda N urulita; Rohadi Ramlan (Politeknik Negeri Sriwijaya, 2021)
Dengue Fever (DBD) is an endemic disease caused by dengue virus with vector of Aedes aegypty mosquito. The disease is still a major health problem in Indonesia. DBD often occurs in communities with high pollution levels such as dirty and unkempt environments. Lack of knowledge about health problems, especially DBD and most of the behavior of the community does not support the 3M movement (draining, burying and closing) is one of the factors that increase the risk of DBD. The increase in dbd cases in Indonesia makes many manufacturers create mosquito repellent products to tools and drugs that can kill mosquitoes with various types of products and brands. But the products that are widely sold in the market, can be said to be less environmentally friendly and sometimes not good for health. KKN students have a work program in an effort to increase public awareness and understanding of DBD by providing counseling about mosquito repellent plants. The plant chosen is lemongrass leaves because mosquitoes do not like the aroma and leaves are easily obtained around the community so that it can be processed into an anti-mosquito spray product and in addition